PT PRIMA LAYANAN NASIONAL ENJINIRING FAIR MARKET VALUE OF EQUITY ANALYSIS RELATED TO INITIAL PUBLIC OFFERING (IPO) PLAN BY RELATIVE VALUATION APPROACH - Ahmad Rizani (International Journal of Social Science and Business, 2017)
PT Prima Layanan Nasional Enjiniring (PT PLN Enjiniring) plans to conduct an initial public offering in 2012 that is intended for business development. Purpose of this research was to estimate the fair market value of equity of PT PLN Enjiniring in the framework of an initial public offering. Fair market value of equity of PT PLN Enjiniring is acquired by using relative valuation method with multiple PER (price to earning ratio), PBV (price to book value) and PSR (price to sales ratio). Information used for this research come from two secondary data from financial reports and other information contained in the annual report 2008-2010 PT PLN Enjiniring years audited by public accountants, comperative financial reports, and company’s stock data comparison. The estimated fair market value of equity of PT PLN Enjiniring per December 31st 2011 by using the method of relative valuation is obtained indication the fair market value of equity amounting to Rp3.048.352.406.030